Africa’s regional and local climate response to stratospheric aerosol injection characteristics - Kumi, Naomi; Mensah, Caleb; Quagraine, Kwesi A.; Patel, Trisha D.; Otu-Larbi, Frederick; Prempeh, Nana Agyemang; Nguvava, Mariam; Nkemelang, Tiro; Abiodun, Babatunde J.; Lennard, Christopher; New, Mark G.; Odoulami, Romaric C. (Frontiers in Climate, 2025)
Future climate projections indicate that Africa will experience significant increases in both mean and extreme temperature indices. These changes will be accompanied by notable shifts in precipitation patterns under a high-emission scenario (RCP8.5). Using climate simulations, this study assesses the potential impact of stratospheric aerosol injection (SAI) on projected mean and extreme temperature and precipitation across the continent. We analysed data from the Stratospheric Aerosol Geoengineering Large Ensemble (GLENS) project, which simulates a set of SAI experiments under RCP8.5 emission scenarios with SO2 injection into the tropical stratosphere at 22.8–25 km altitude (GLENS) and around 1 km above the tropopause (GLENS_low) and near the equator at around 20–25 km above ground (GLENS_eq). The results show that all SAI experiments (GLENS, GLENS_eq, and GLENS_low) exhibit substantial cooling effects, with GLENS_eq emerging as the most effective in reducing temperature extremes, particularly over Central and Southern Africa. However, despite successfully offsetting much of the RCP8.5-induced warming, the effectiveness of SAI varies across regions, leaving some regions, such as the Sahel and North Africa, with residual warming. In addition to its cooling effects, SAI could significantly alter precipitation patterns, introducing widespread drying and thereby reducing flood risks across the continent. While SAI could offset the projected increase in extreme precipitation under RCP8.5, it could simultaneously exacerbate drying trends over Central, Southern, and Northern Africa. These findings highlight critical trade-offs associated with SAI deployment, particularly for regions where agriculture and water resources depend heavily on rainfall, underscoring the need for regionally optimised geoengineering strategies that balance temperature moderation with hydrological stability. This study provides the first comparative analysis of tropical, equatorial, and low-altitude SAI impacts on the climate, revealing critical trade-offs for precipitation-dependent regions. The findings presented here are, however, specific to the SAI scenarios analysed (GLENS experiments), as a different SAI deployment scenario would lead to different conclusions.